Simultaneous determination of thorium and uranium in mineral fertilizers by inductively coupled plasma optical emission spectrometry - Souza, Sidnei O.; Ávila, Dayara V. L.; Monteiro, Adnívia S. C. [UNESP]; Garcia, Carlos Alexandre B.; Alves, José P. H.; Maranhão, Tatiane A.; Araujo, Rennan G. O. (Sociedade Brasileira de Quimica (SBQ), 2016)
The simultaneous determination of thorium and uranium in mineral fertilizers by inductively coupled plasma optical emission spectrometry (ICP OES) was optimized. The three-level factorial design was applied to optimize the operating conditions of radiofrequency power and nebulizer gas flow rate. The analytical method was specific and selective for both elements.
Keywords: Experimental design; ICP OES; Simultaneous determination; Thorium; Uranium